0234 Head and neck cancer and occupational exposure to asbestos, mineral wools and silica: results from the ICARE study. (23rd June 2014) - Paget-Bailly, Sophie; Cyr, Diane; Carton, Matthieu; Guida, Florence; Stucker, Isabelle; Luce, Danièle
Abstract : Objectives: To study the associations between head and neck cancer risk and occupational exposure to asbestos, mineral wools and silica. Method: ICARE is a population based case-control study conducted in France. Analyses were restricted to men and included 1833 cases of head and neck squamous cell carcinomas (HNSCC) and 2747 controls. Complete occupational history was collected. Occupational exposures were assessed through job-exposure matrices. Logistic models were used to estimate adjusted odds ratios (ORs) and 95% confidence intervals (CI). Results: Exposure to asbestos was associated with an elevated risk of HNSCC (OR=1.9, CI 1.6–2.3), and the risk increased significantly with the probability, duration and cumulative level of exposure. Significantly increased risks were found for all cancer sites: larynx (OR=2.1, CI 1.6–2.8), hypopharynx (OR=2.0 CI 1.5–2.8), oropharynx (OR=1.6 CI=1.3–2.1) and oral cavity (OR=1.9 CI 1.4–2.6). Conversely, after adjustment for asbestos exposure, exposure to mineral wools was not associated with HNSCC risk (OR=0.8 CI 0.6–1.0), for any of the cancer sites. Exposure to silica was not associated with HNSCC risk overall (OR=0.9 CI 0.7–1.2), but non-significantly elevated ORs were observed for the highest level of cumulative exposure for oropharyngeal (OR=1.6 CI 0.8–3.2) and hypopharyngeal cancer (OR=1.9 CI 0.9–4.1). Conclusions: Our findings confirm the role of asbestos exposure in laryngeal cancer, and suggest that asbestos exposure increases also the risk of oral and pharyngeal cancer. There is some evidence of an association between silica exposure and pharyngeal cancer. Exposure to mineral wools was not associated with HNSCC risk in our study.